Factors Conducive to Catch-Up Growth in Postoperative Jejunoileal Atresia Patients as Prognostic Markers of Outcome - Shibuya, Soichi; Koga, Hiroyuki; Lane, Geoffrey J.; Yamataka, Atsuyuki (European Journal of Pediatric Surgery, 2016)
Introduction Jejunoileal atresia (JIA) is a major congenital anomaly that requires surgical intervention in the neonatal period. During follow-up after surgery, there is usually a period of catch-up growth (CUG) that is sufficient for patients to regain normal weight for age. However, in some cases, CUG is inadequate. The aim of this study was to assess postoperative JIA patients to determine factors that may be associated with good CUG.Material and Methods We retrospectively reviewed JIA patients treated at our institution by classifying them into three groups based on a comparison of postoperative weight with standard weight for healthy matched controls; that is, more than mean at 12 months after surgery (group M+), less than mean at 12 months after surgery but more than mean at 24 months after surgery because of CUG (group M-CUG+), less than mean at 24 months after surgery because there was no CUG (group M-CUG−). The following parameters were evaluated: gestational age, birth weight, sight of atresia: jejunum or ileum, length of residual small intestine, ratio of the length of residual small intestine to the predicted length of small intestine for matched gestational age (RP ratio), and duration of parenteral nutrition.Results A total of 42 patients were reviewed and classified into group M+ (n = 13), group M-CUG+ (n = 11), and group M-CUG− (n = 18). There were no significant differences in gestational age, birth weight, and duration of parenteral nutrition between the three groups. Incidence of JIA according to site was also similar. Length of residual small intestine was not significantly different between the three groups, but RP ratios were significantly higher in M+ (84.7 ± 15.4%) and M-CUG+ (83.8 ± 17.7%) compared with M-CUG− (69.2 ± 18.1%) (p = 0.02, respectively).Conclusions A higher RP ratio (approximately 84%) would appear to be conducive to CUG while a lower ratio (less than 70%) was not. Actual length of residual small intestine was not relevant to CUG. We recommend calculating the RP ratio in postoperative JIA patients and using 70% as a cutoff value to predict patients with poor potential for CUG who may benefit from more aggressive nutritional support to achieve normal growth.
Keywords: jejunoileal atresia; catch-up growth; length of residual small intestine; predicted length of small intestine